Algorithmic regulation: A maturing concept for investigating regulation of and through algorithms - Lena Ulbricht; Karen Yeung (Regulation & Governance, 2022)
This paper offers a critical synthesis of the articles in this Special Issue with a view to assessing the concept of “algorithmic regulation” as a mode of social coordination and control articulated by Yeung in 2017. We highlight significant changes in public debate about the role of algorithms in society occurring in the last five years. We also highlight prominent themes that emerge from the contributions, illuminating what is distinctive about the concept of algorithmic regulation, reflecting upon some of its strengths, limitations, and its relationship with the broader research field. In closing, we argue that the core concept is valuable and maturing. It has evolved into an analytical bridge that fosters cross-disciplinary development and analysis in ways that enrich its early “skeletal” form, thereby enabling careful and context-sensitive analysis of algorithmic regulation in concrete settings while facilitating critical reflection concerning the legitimacy of existing and proposed regulatory regimes.
Keywords: 320; accountability; data protection; ethics; platform capitalism; surveillance